2011
DOI: 10.1371/journal.pone.0019437
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Field Effect or Simply Stress? Effects of UMTS Exposure on Hippocampal Longterm Plasticity in the Context of Procedure Related Hormone Release

Abstract: Harmful effects of electromagnetic fields (EMF) on cognitive and behavioural features of humans and rodents have been controversially discussed and raised persistent concern about adverse effects of EMF on general brain functions. In the present study we applied radio-frequency (RF) signals of the Universal Mobile Telecommunications System (UMTS) to full brain exposed male Wistar rats in order to elaborate putative influences on stress hormone release (corticosteron; CORT and adrenocorticotropic hormone; ACTH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 73 publications
0
14
1
Order By: Relevance
“…The increased CORT levels found in GSM-exposed 6 week-old rats were not in accordance with the literature showing the absence of a CORT levels modification relative to EMF exposure in in vivo studies in adult Fischer 344 and Wistar rats (Prochnow et al, 2011;Stagg et al, 2001). However, previous studies showed middle-aged related differences in plasmatic CORT or corticotropin-releasing factor responses to different types of stress when compared to young animals (Nolan et al, 1991;Pisarska et al, 2000).…”
Section: Gsm Exposure Stress and Emotional Memorycontrasting
confidence: 76%
“…The increased CORT levels found in GSM-exposed 6 week-old rats were not in accordance with the literature showing the absence of a CORT levels modification relative to EMF exposure in in vivo studies in adult Fischer 344 and Wistar rats (Prochnow et al, 2011;Stagg et al, 2001). However, previous studies showed middle-aged related differences in plasmatic CORT or corticotropin-releasing factor responses to different types of stress when compared to young animals (Nolan et al, 1991;Pisarska et al, 2000).…”
Section: Gsm Exposure Stress and Emotional Memorycontrasting
confidence: 76%
“…and summarized in table S1. LTP responses were analyzed as described [26]. All values are expressed as mean ± standard error of the mean (s.e.m.).…”
Section: Methodsmentioning
confidence: 99%
“…In our study we found the level of this hormone to increase considerably in both, embryos as well as in the newly hatched chicks exposed to electromagnetic field during incubation (Figure 4). The stress-inducing action of electromagnetic field was implicated in the studies with rats, where corticosterone concentrations were also observed to increase as a response to RF-EMF [17,28,29].…”
Section: Discussionmentioning
confidence: 99%